Pentingnya Membangun Kesadaran Hukum Bagi Generasi Muda - Sulastri; Setiana, Eka (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2025)
Legal awareness is a fundamental aspect in shaping an orderly and just society, especially among the younger generation as the future leaders of the nation. In the current era of globalization, various external cultural influences and technological developments have caused a shift in values that has the potential to weaken compliance with the law. This phenomenon can be seen in the large number of students who violate rules, such as riding a motorcycle without wearing a helmet or not having a driver's license. Based on these conditions, as part of the implementation of the three pillars of higher education, lecturers and students of the Pancasila and Citizenship Education Study Program at Pamulang University organized a Community Service (PKM) activity at SMAN 3 South Tangerang City with the theme “Education to Increase Legal Awareness for the Younger Generation.” In its implementation, this activity applied a socialization and counseling approach based on interaction as a medium for legal learning aimed at increasing participants' understanding of the meaning and urgency of legal awareness in social life. The results of the activity showed that most students did not fully understand legal regulations and had not implemented them in their daily lives. Through this activity, students gained a new understanding of the importance of law and were encouraged to apply the values of discipline and responsibility in social life. Thus, legal education in schools is a strategic step in building a culture of legal awareness among Indonesia's younger generation.